Geometry and development of the ice-cored ridges in the Kutno Moraine: evidence from lithofacies and deformation structures of supraglacial deposits in Daszyna site - Włodarski, Wojciech; Orłowska, Anna; Wasiluk, Radosław (Acta Geographica Lodziensia, 2024)
The ice-cored ridges are important for palaeogeographical studies of retreating margins of glaciers. Earlier reconstructions of ice-cored ridges in marginal zones of the Pleistocene ice-sheets have been made based on sedimentological studies. Applying such approach, research were able only to show in which degree depressions between ice-cored ridges influenced spatial variations in depositional processes. There is possible to determine more precise characteristics of ice-cored ridges geometry based on detailed analysis of collapse structures. The shape, elongation and orientation of ice-cored ridges can be derived from geometry and kinematics of folds and faults as major elements of the collapse structures. Integration sedimentological studies of supraglacial deposits with analysis of collapse structures also allows to determine the evolution of ice-cored ridges up to final deicing. This approach is the subject of case study performed in Daszyna site located in the Kutno Moraine.